Cost-Benefit Analysis of POME Biogas Power Plant: Case Study of PLTBg Suka Damai - Donny Yoesgiantoro (Institut Teknologi Sepuluh Nopember, 2020)
Palm Oil Mill Effluent (POME) is a byproduct of processing fresh palm fruit bunches into crude palm oil (CPO) which has negative externalities in the form of gas containing methane, carbon dioxide and other greenhouse gases (GHG) which is very dangerous for sustainability environment. The use of pome as feedstocks for biogas power plants (PLTBg) changes the negative externalities of pome into positive externalities such as increased electrification in the area around the palm oil mill (PKS) and also good for environmental sustainability. PLTBg Suka Damai with a capacity of 2.4 Mw is planned to reach the Commercial Operating Date (COD) in 2019, the financial calculation has a cost-benefit ratio of 1.19, percentage of Internal Rate of Return (IRR) of 12.84%, percentage of weighted cost of capital (WACC) 10% and a Net Present Value (NPV) of Rp 21,275,609,209.00. Using the cost-benefit analysis method, the authors calculate the positive externalities generated by PLTBg Suka Damai by comparing the value of benefits into three (3) alternative scenarios. The scenario I add the social cost of carbon (SCOC) as additional benefits; scenario II adds carbon credit income parameters from the REDD+ scheme; scenario III only utilizes the benefits of electricity sales and the electrification without adding additional benefits. Comprehending all the results, the first scenario with SCOC is the most optimize scenario for it provides far greater benefits to the community, far greater than the financial revenue received by the PLTBg itself.